Teacher’s Directive Speech Acts at Kindergarten School - Kharisma Puspita Sari (Universitas Islam Negeri Walisongo Semarang, 2018)
The research is field research with descriptive qualitative research. The research aims to determine and investigate the teacher's directive speech acts at kindergarten school. The research investigates a teacher in a day of teaching-learning activity at kindergartenschool. Deeply, the research investigates a whole sequence of activity in the class. Actually, there are 6 sessions of the learning activity determined such as; 1) forming in line, 2) circle time, 3) praying up, 4) learning activity, 5) take a rest, 6) learning evaluation and review, 7) praying up, 8) singing a song, 9) closing session. From this sequence of activities, there are three types of directive speech acts which is often used by teacher at certain kindergarten school like requests, requirements, and questions. Specifically, there are several types of directive speech acts in details used by the teacher such as asking, interrogating, inquiring, invite, command, order, hope, suggest, prohibit, advice, and others.